Piper crocatum and Aloe vera Difference Effectiveness in Complementary Treatment of Perineal Wounds - Mubayyina, Firdaus; Alam, Gemini; Usman, Andi Nilawati; Ahmad, Mardiana; As’ad, Suryani; Raya, Indah (Universitas Islam Negeri Mataram, 2022)
Indonesia, with a maternal mortality rate (MMR) of 305 per 100,000 live births, is directly caused by post-partum hemorrhage (30.3%) and hypertension (27.1%). At the same time, post-partum infection ranks second as a contributor to maternal death after bleeding. Data from the Indonesian Demographic Health Survey (IDHS) showed that the incidence of perineal laceration or rupture was experienced by women who gave birth vaginally (75%). The prevalence of women who experience perineal tears is in the 25-30 years (24%) and women aged 32-39 years (62%). This study aimed to examine the differences in the effectiveness of Piper crocatum and Aloe vera in the complementary treatment of perineal wound healing in post-partum mothers. This study was a quasi-experimental pretest-posttest control group design with a total sampling method with a ratio of 1:1:1 for as many as 30 post-partum mothers with grade I and II injuries according to inclusion criteria with Intervention group red betel stew, aloe vera, and the Control group with perineal injuries at Gunung Sari Health Center and Sesela Health Center. The data observed were the degree of perineal wound healing using the REEDA scale (Redness, Edema, Ecchymosis, Discharge, and Approximation). The results showed differences in the effectiveness of Piper crocatum and aloe vera on perineal wound healing. The average results of the Mann-Whitney statistical test were on the 5th and 7th days (p-value< 0.005). This study shows that Piper crocatum can accelerate the healing of perineal wounds and become an alternative, complementary therapy in perineal wound healing.